(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2012)
A comprehensive summary of papers contained in this book can be found in its Introduction (pp. xii–xv), and I have nothing new to add to that excellent overview. I will focus instead on some issues that can be derived from discussions made in some (or most) of the articles in the book – for example, why are the activities of certain radical socio-political movements considered as "aesthetics", and do we simply approach them from the aesthetic perspective or consider them as "artworks".